Factors that contribute to customers loyalty towards nutrilite: A case study in Cheras, Kuala Lumpur / Nur Syafiqah Alia Muhamad Ali - Muhamad Ali, Nur Syafiqah Alia (Faculty of Business and Management, 2008)
Health industry needs to remain competitive. One way of improving competitive advantage is to attract more customers and increase customer loyalty. For example by developing long term, secure relationship between the buyers and sellers. Thus, this study has been conducted to determine how to build customer loyalty towards Nutrilite. The objective of this study is to rank the factors that influence customers' loyalty. Besides that, this study also determines the satisfaction of the customer with the value given by Nutrilite through its price, brand, quality and customer experience. Then, this study can give suggestions and recommendation to Nutrilite to ensure customers' loyalty towards its products. In collecting data, the researcher used primary data (questionnaire) as a way to get feedback from the customers. By using Non Probability Sampling, the researcher has selected 242 respondents to participate on this study. Moreover, the sample populations were respondents who purchase Nutrilite. Then, the researcher has categorized this study as descriptive for research design method. Next, the data gathered was analysed by using the Statistical Package for Social Science (SPSS) Version 14. Then, all the data was interpreted and test by frequency distribution analysis, cross tabulation, ANOVA analysis, Correlations and Regression Analysis. The finding shows that all the independent variables have an association with dependent variables (customer loyalty) toward.Nutrilite. From the findings, it shows that branding is the most important factors in contributing customers' loyalty towards Nutrilite while price is the least important factors. Some conclusions are provided in the research and the researcher also stated several recommendations, which are to improve the customer loyalty towards Nutrilite. It is a great pleasure if Nutrilite is willing to evaluate the suggestions from the respondents and the researcher